Comparison of different prognostic scores for risk stratification in septic patients arriving to the Emergency Department - Valeria Caramello (Italian Journal of Medicine, 2020)
We evaluated the prognostic performance of systemic inflammatory response syndrome (SIRS), sequential organ failure assessment (SOFA), quick-SOFA (qSOFA), modified early warning score (MEWS), lactates and procalcitonin in septic patients. Prospective study on adults with sepsis in the Emergency Department (ED). Area under the Receiver operator characteristic curve (AUC) was calculated to assess how scores predict mortality at 30 and 60 days (d) and upon admission to Intensive care unit (ICU). Among 469 patients, mortality was associated with higher SOFA, qSOFA, MEWS and lactates level. ICU admission was associated with higher SOFA, procalcitonin and MEWS. Prognostic performance for mortality were: SOFA AUC 30 d 0.76 (0.69-0.81); 60 d 0.74 (0.68-0.79); qSOFA AUC 30 d 0.72 (0.66-0.79); 60 d 0.73 (0.67-0.78) and lactates AUC 30 d 0.71 (0.60-0.82); 60d 0.65 (0.54- 0.73). For the outcome ICU admission, procalcitonin had the highest AUC [0.66 (0.56-0.64], followed by SOFA [0.61 (0.54-0.69)] and MEWS [0.60 (0.53-0.67)]. SOFA, qSOFA and lactates assessment after arrival in the ED have a good performance in detecting patients at risk of mortality for sepsis. Procalcitonin is useful to select patients that will need ICU admission.